The impact of virtual communication technologies on international business traveling : experiences of four business managers - Matikainen, Anna (My University, 2020)
International business traveling plays a considerable role in many organizations. Especially due to globalization, many organizations have subsidiaries as well as business partners across the world, forcing their employees to travel abroad in order to attend business meetings, conferences and to close deals, for example. During the years, there have been numerous developments in virtual communication technologies (e.g. e-mails, Microsoft Surface Hub, Skype, Slack and videoconference), enabling organizations to handle some of their meetings virtually without the need of traveling for a face-to-face meeting. Still, even with all the advancements in these technologies, the amount of international business traveling keeps increasing annually. In order to understand the need behind traveling and why it is chosen over virtual communication technologies, it is important to under-stand how the decisions are actually made between these two options. The objective of this study was to find out what affects the decision-making process between inter-national business traveling and virtual communication technologies from international business travelers’ perspective. Thus, this study aims to find out how the decisions are made and what aspects influence the process. The data was collected by interviewing four international business travelers who have traveled for a long time and still travel on regular intervals both domestically but especially internationally as a part of their job. The results support the findings of earlier empirical research on the topic for most part, but also brings out new aspects on the decision-making process between virtual communication technologies and international business traveling. The findings show that purpose of the meeting as well as the relation between meeting participants are the most important factors when making the decision. Furthermore, time, message, location and a new dimension, environment, were found to have an impact in various ways. Lastly, the findings show some important take-aways for managers and directors for how to better understand, manage and guide the international business traveling process from within the organization.

Kansainvälisellä työmatkustamisella on merkittävä rooli monissa nykypäivän organisaatioissa. Erityisesti globalisaation myötä monilla yrityksillä on tytäryhtiöitä ja yrityskumppaneita ympäri maailmaa, joka puolestaan ajaa työntekijöitä ulkomaille osallistumaan muun muassa erilaisiin tapaamisiin, konferensseihin ja tekemään kauppoja. Viime vuosien aikana myös virtuaaliset kommunikaatioteknologiat ovat kehittyneet (esimerkiksi sähköposti, Microsoft Surface Hub, Skype, Slack ja videokonferenssit), tarjoten yrityksille mahdollisuuden osallistua erinäisiin kokouksiin virtuaalisesti sen sijaan, että olisi aina matkustettava tapaamisia varten. Viimeaikaisista kehityksistä huolimatta kansainvälisen työmatkustamisen määrä kasvaa yhä vuosittain. Jotta voisimme ymmärtää paremmin tarvetta matkustamisen takana ja miksi siihen turvaudutaan virtuaalisten kommunikaatioteknologioiden sijaan, on tärkeää selvittää, kuinka päätöksiä näiden kahden eri vaihtoehdon välillä tehdään. Tutkimuksen tarkoituksena oli selvittää mitkä tekijät vaikuttavat päätöksentekoprosessiin kansainvälisen työmatkustamisen ja virtuaalisten kommunikaatioteknologioiden välillä kansainvälisten työmatkustajien näkökulmasta. Täten tutkimus pyrki selvittämään, kuinka päätöksiä tehdään ja mitkä eri aspektit vaikuttavat tähän prosessiin. Tutkimuksen data kerättiin haastattelemalla neljää kansainvälistä työmatkustajaa, jotka ovat matkustaneet jo kauan ja jotka yhä matkustavat työstänsä johtuen säännöllisin väliajoin sekä kotimaassa, mutta erityisesti ulkomailla. Tulokset tukevat suurimmilta osin aiempien empiiristen tutkimusten löydöksiä, esitellen lisäksi uusia näkökulmia päätöksentekoprosessiin virtuaalisten kommunikaatioteknologioiden ja kansainvälisen työmatkustamisen välillä. Tulokset osoittavat, että tapaamisen tarkoitus ja osallistujien välinen suhde ovat tärkeimmät tapaamistavan määrittelevät tekijät. Näiden lisäksi aika, viesti, sijainti ja uutena aspektina ympäristö vaikuttavat erinäisillä tavoilla päätöksentekoprosessiin. Viimeiseksi, johtopäätökset esittelevät tärkeitä huomioita managereille ja johtajille siitä, kuinka he voisivat paremmin ymmärtää ja johtaa kansainvälisen työmatkustamisen vaiheita omassa organisaatiossaan.
Keywords: International business travelers, virtual communication technologies, meetings